2015
DOI: 10.1155/2015/362936
|View full text |Cite
|
Sign up to set email alerts
|

Alternations in Cholesterol and Fatty Acids Composition in Egg Yolk of Rhode Island Red x Fyoumi Hens Fed with Hemp Seeds (Cannabis sativaL.)

Abstract: The present study was designed to evaluate the influence of hemp seed (HS) supplementation on egg yolk cholesterol and fatty acid composition in laying hens. Sixty hens (Rhode Island Red x Fyoumi) were evenly distributed into four groups (three replicates per group) at the peak production (34 weeks). HS was included into the ration at the level of 0.0 (HS-0), 15 (HS-15), 20 (HS-20), and 25% (HS-25) and continued the supplementation for consecutively three weeks. At the end of the experiment, three eggs per rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 23 publications
4
19
1
Order By: Relevance
“…It has been hypothesized that the inability to markedly reduce egg cholesterol levels is due to a physiological control mechanism that ultimately causes the cessation of egg production when yolk cholesterol deposition is inadequate for embryo survival (Ceylan et al, 2011). In contrast to our finding, the study conducted by Shahid et al (2015) showed that the yolk cholesterol level of laying hens whose diet had been treated with hemp seed at a rate of 15% -25% was significantly lower (P <0.05), compared to the control group. The results of a study by Johansson (2010) suggest that hemp seed may lower the cholesterol levels in egg yolk.…”
Section: Resultscontrasting
confidence: 99%
“…It has been hypothesized that the inability to markedly reduce egg cholesterol levels is due to a physiological control mechanism that ultimately causes the cessation of egg production when yolk cholesterol deposition is inadequate for embryo survival (Ceylan et al, 2011). In contrast to our finding, the study conducted by Shahid et al (2015) showed that the yolk cholesterol level of laying hens whose diet had been treated with hemp seed at a rate of 15% -25% was significantly lower (P <0.05), compared to the control group. The results of a study by Johansson (2010) suggest that hemp seed may lower the cholesterol levels in egg yolk.…”
Section: Resultscontrasting
confidence: 99%
“…In addition, literature reports agree that the inclusion of hempseed products to the poultry diet effectively improved the nutritional value of the eggs and meat and obtained food products with higher total n-3 PUFAs amount, higher PUFA/SFA ratio, and a better-balanced n-6/n-3 PUFAs ratio in comparison to the poultry food products obtained by animals fed a normal diet. More specifically, it has been demonstrated that the total n-3 PUFAs and the individual n-3 PUFA ALA, as well as the n-3 LCPUFAs biologically active in humans, namely EPA, DPA (Docosapentaenoic Acid), and DHA, were increased in both poultry eggs [ 150 , 152 , 153 , 156 , 157 , 158 , 159 , 160 ] and meat (thigh and breast) [ 150 ] as the inclusion of the hemp products rose and the n-6/n-3 PUFAs ratio, normally high in common eggs, was reduced [ 152 , 157 , 158 , 161 ]. Neijat and colleagues [ 157 ] found that, as a consequence of the dietary hempseed and hempseed oil supplementation to the laying hens’ control diet (wheat-barley-soybean meal-based), the ALA content increased in a dose-dependent manner and this increase was higher in the TGs than in the phospholipids (PLs) that, therefore, seem to be less responsive in ALA enrichment in comparison to TGs.…”
Section: Hempseed Foodsmentioning
confidence: 99%
“…Fatty acid methyl esters (FAME) were measured according to the method of Shahid et al (2015). Briefly, 50 mg egg yolk was mixed with 1.5 mL of methanolic sodium hydroxide and boiled at 100 • C for 5 min.…”
Section: Determination Of Fatty Acidmentioning
confidence: 99%
“…The function of essential fatty acids (linoleic and alphalinolenic acid) and their metabolites in human and animal health is a subject of scientific attention today (Shahid et al, 2015). Because of inadequate ω-3 polyunsaturated fatty acid intake in the human diet, research work has been focused on producing animal food products enriched with a healthy fatty acid profile (Cherian, 2002;Kang, 2008).…”
Section: Introductionmentioning
confidence: 99%